A production-based model for a fractured well in unconventional reservoirs - Mohammed, Shaibu; Anumah, Prosper; Sarkodie-kyeremeh, Justice; Acheaw, Emmanuel (My University, 2020)
Due to the depletion of conventional reservoirs and the high demand of energy, unconventional reservoirs will be relied on to supply the world’s energy for the foreseeable future. Unfortunately, modelling and analysis of these reservoirs have been very challenging because of their complex storage and flow mechanisms. Although analytical, semi-analytical and numerical models have been proposed, these models rely on simplifying assumptions and require several input parameters. In this paper, a production-based model is proposed to analyze and predict a fractured-well performance in unconventional reservoirs. The model assumes a power law with a stretched exponential cut-off. While the power-law term governs the transient-state period, the stretched exponential term, which is a superposition of exponential decays, governs the boundary-dominated flow period. As a result, the model is capable of matching both the transient state and boundary-dominated flow portions of the data. The model has been validated with a numerical data and applied to several field data; in addition, the model has been used to estimate P10, P50 and P90 values, as well as to develop P10, P50 and P90 type curves for the Barnett shale. These type curves will be useful for production forecasting of new wells in the field or analogue fields. Results of the model have been compared with existing models. The findings show that the proposed model yields relatively good reserve estimates, and predicts the future production performance of unconventional reservoirs not only during the transient-state period, but also the boundary-dominated flow period. The proposed model may contribute to the ongoing efforts to improve the analysis and forecasting of fractured-well performance in unconventional reservoirs.
Keywords: Unconventional reservoirs; Fractured-well performance; Production-based model; Reserve estimate; P90; P50 and P10 type curves; Barnett shale